Pengaruh Tunjangan Kinerja dan Disiplin Kerja terhadap Kinerja Pegawai Kantor Otoritas Bandar Udara Wilayah I Kelas Utama di Tangerang - Eva Atyk Umyaty; Hira Maulida (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstrak. The purpose of this study is to determine the extent to which performance allowances and work discipline influence employee performance at the Office of the Airport Authority Region I Main Class in Tangerang, both partially and simultaneously. This research employs a quantitative research method with a descriptive quantitative approach. The sampling technique used in this study was simple random sampling. To determine the sample size, the Slovin formula was applied, which is commonly used to calculate the appropriate number of samples to be studied. Based on this formula, out of a total population of 120, a sample of 92 respondents was obtained. Data analysis includes validity testing, reliability testing, classical assumption testing, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results indicate a positive influence between performance allowances and employee performance when examined partially. The simple linear regression equation is: Y = 27.971 + 0.422 X₁, with a correlation coefficient of 0.672, which falls within the interval 0.60–0.799, indicating a strong relationship between the two variables. The coefficient of determination shows a contribution of 50%, while the remaining 50% is influenced by other factors. The hypothesis test shows that t-count > t-table (8.620 > 1.663), thus H₀₁ is rejected and Hₐ₁ is accepted. The results also demonstrate a positive influence between work discipline and employee performance when examined partially. The simple linear regression equation is: Y = 28.164 + 0.420 X₂, with a correlation coefficient of 0.643, also indicating a strong relationship. The coefficient of determination is again 50%, with the remaining 50% influenced by other factors. The hypothesis test shows t-count > t-table (7.966 > 1.663), therefore H₀₂ is rejected and Hₐ₂ is accepted. Furthermore, the findings show that there is a positive and significant simultaneous influence between performance allowance and work discipline on employee performance. The multiple linear regression equation is: Y = 14.370 + 0.408 X₁ + 0.406 X₂, with a correlation coefficient of 0.915, which falls within the interval 0.80–1.000, indicating a very strong relationship. The coefficient of determination shows a simultaneous contribution of 83.7%, while the remaining 16.3% is affected by other variables. The hypothesis test shows F-count > F-table (228.578 > 3.11), meaning it can be concluded that performance allowance and work discipline significantly influence employee performance.